HO-1 in Bone Biology: Potential Therapeutic Strategies for Osteoporosis - Zhou, Xueman; Yuan, Wenxiu; Xiong, Xin; Zhang, Zhenzhen; Liu, Jiaqi; Zheng, Yingcheng; Wang, Jun; Liu, Jin (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis is a prevalent bone disorder characterized by bone mass reduction and deterioration of bone microarchitecture leading to bone fragility and fracture risk. In recent decades, knowledge regarding the etiological mechanisms emphasizes that inflammation, oxidative stress and senescence of bone cells contribute to the development of osteoporosis. Studies have demonstrated that heme oxygenase 1 (HO-1), an inducible enzyme catalyzing heme degradation, exhibits anti-inflammatory, anti-oxidative stress and anti-apoptosis properties. Emerging evidence has revealed that HO-1 is critical in the maintenance of bone homeostasis, making HO-1 a potential target for osteoporosis treatment. In this Review, we aim to provide an introduction to current knowledge of HO-1 biology and its regulation, focusing specifically on its roles in bone homeostasis and osteoporosis. We also examine the potential of HO-1-based pharmacological therapeutics for osteoporosis and issues faced during clinical translation.